Character Values In Block-Building Play At Tk Bhayangkari 26 Bengkulu City Among Children Aged 5–6 Years - Viola Tri Amelia; Ahmad Suradi; Budrianto (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to identify the character values that emerge through block-building play activities among children aged 5–6 years at TK Bhayangkari 26 Bengkulu City. The research method used was descriptive quantitative research. The research subjects consisted of 20 Group B children aged 5–6 years. Data were collected through observation using an observation sheet containing character value indicators, namely discipline, responsibility, cooperation, honesty, independence, and creativity. The data were analyzed using descriptive statistics in the form of percentages. The results of the study showed that block-building play was able to foster various character values in children. The most dominant character values were cooperation and responsibility, while the character values that still need improvement were honesty and discipline. Therefore, block-building play can serve as an effective learning activity for instilling character values in early childhood.